Cost-effectiveness analysis measuring the total costs against the health benefits of three different rotavirus vaccines for Mexico - Jorge Gomez; F. Raul Velázquez; Adriana Guzman-Holst; Maria Yolanda Cervantes Apolinar; Laure-Anne Van Bellinghen; Ilse Van Vlaenderen; Désirée van Oorschot (Taylor & Francis Group, 2023)
Rotavirus (RV) infection causes acute rotavirus gastroenteritis (RVGE) in infants. Safe and effective RV vaccines are available, of which Mexico has included one in its national immunization program (NIP) since 2007. Health outcome gains, expressed in quality-adjusted life years (QALYs), and cost improvements are important additional factors for the selection of a NIP vaccine. These two factors were analyzed here for Mexico over one year implementing three RV vaccines: 2-dose Rotarix (HRV), versus 3-dose RotaTeq (HBRV), and 3-dose Rotasiil (BRV-PV), presented in a 1-dose or 2-dose vial). HRV would annually result in discounted QALY gains of 263 extra years compared with the other vaccines by averting an extra 24,022 homecare cases, 10,779 medical visits, 392 hospitalizations, and 12 deaths. From a payer's perspective and compared with HRV, BRV-PV 2-dose vial and BRV-PV 1-dose vial would annually result in $13,548,179 and $4,633,957 net savings, respectively, while HBRV would result in $3,403,309 extra costs. The societal perspective may also show savings compared with HRV for BRV-PV 2-dose vial of $4,875,860, while BRV-PV 1-dose vial and HBRV may show extra costs of $4,038,363 and $12,075,629 respectively. HRV and HBRV were both approved in Mexico, with HRV requiring less investment than HBRV with higher QALY gains and cost savings. The HRV vaccine produced those higher health gains due to its earlier protection and greater coverage achieved after its schedule completion with two doses only, providing full protection at four months of age instead of longer periods for the other vaccines.